FgPex3, a Peroxisome Biogenesis Factor, Is Involved in Regulating Vegetative Growth, Conidiation, Sexual Development, and Virulence in Fusarium graminearum - Kong, Xiangjiu; Zhang, Hao; Wang, Xiaoliang; van der Lee, Theo; Waalwijk, Cees; van Diepeningen, Anne; Brankovics, Balazs; Xu, Jin; Xu, Jingsheng; Chen, Wanquan; Feng, Jie (Frontiers in Microbiology, 2019)
Peroxisomes are involved in a wide range of important cellular functions. Here, the role of the peroxisomal membrane protein PEX3 in the plant-pathogen and mycotoxin producer Fusarium graminearum was studied using knock-out and complemented strains. To fluorescently label peroxisomes’ punctate structures, GFP and RFP fusions with the PTS1 and PTS2 localization signal were transformed into the wild type PH-1 and ΔFgPex3 knock-out strains. The GFP and RFP transformants in the ΔFgPex3 background showed a diffuse fluorescence pattern across the cytoplasm suggesting the absence of mature peroxisomes. The ΔFgPex3 strain showed a minor, non-significant reduction in growth on various sugar carbon sources. In contrast, deletion of FgPex3 affected fatty acid β-oxidation in F. graminearum and significantly reduced the utilization of fatty acids. Furthermore, the ΔFgPex3 mutant was sensitive to osmotic stressors as well as to cell wall-damaging agents. Reactive oxygen species (ROS) levels in the mutant had increased significantly, which may be linked to the reduced longevity of cultured strains. The mutant also showed reduced production of conidiospores, while sexual reproduction was completely impaired. The pathogenicity of ΔFgPex3, especially during the process of systemic infection, was strongly reduced on both tomato and on wheat, while to production of deoxynivalenol (DON), an important factor for virulence, appeared to be unaffected.